Platelet-rich emboli are associated with von Willebrand factor levels and have poorer revascularization outcomes. (4th November 2019) - Douglas, Andrew; Fitzgerald, Seán; Mereuta, Oana Madalina; Rossi, Rosanna; O'Leary, Sean; Pandit, Abhay; McCarthy, Ray; Gilvarry, Michael; Holmegaard, Lukas; Abrahamsson, Margareta; Jerndal, Mikael; Dehlfors, Niclas; et al.
Abstract : Background and aims: Platelets and von Willebrand factor (vWF) are key factors in thrombosis and thus are likely key components of acute ischemic stroke (AIS) emboli. We aimed to characterize platelet and vWF levels in AIS emboli and to assess associations between their expression levels and clinical and procedural information. Materials and method: Histopathological and immunohistochemical analysis of emboli collected as part of the multi-institutional RESTORE registry was performed. The composition of the emboli was quantified using Orbit Image Analysis machine learning software. Correlations between clot components and clinical and procedural information were assessed using the χ 2 test. Results: Ninety-one emboli samples retrieved from 63 patients were analyzed in the study. The mean platelet (CD42b) content of the clots was 33.9% and the mean vWF content of the clots was 29.8%. There was a positive correlation between platelet and vWF levels (ρ=0.564, p<0.001*, n=91). There was an inverse correlation between both platelets and vWF levels and percentage of red blood cells (RBCs) in the emboli (CD42b vs RBC: ρ=−0.535, p<0.001*, n=91; vWF vs RBC: ρ=−0.366, p<0.001*, n=91). Eighty-one percent of patients in the low platelet group had a good revascularization outcome (Thrombolysis in Cerebral Infarction 2c/3) compared with 58% in the high platelet group (χ 2 =5.856, p=0.016). Conclusion: Platelet and vWF levels in AIS emboli correlate with each other and both have an inverse relationship with RBC composition. Patients with platelet-rich clots have poorer revascularization outcomes.